Ensuring Secured Multicast Group Communications for Wireless Sensor Networks using Efficient Key Distribution Schemes - Devi, S Sasikala (International Journal of Computer Sciences and Engineering, 2020)
Multicast is the only prominent method for transmitting data from a single source to several known destinations. More than ever, in wireless sensor networks, with the help of unguided medium, a single transmission able to be received by all nodes within a transmission range. A wireless sensor network (WSN) are spatially distributed autonomous sensors to monitor physical or environmental conditions, such as temperature, sound, pressure, etc. and to cooperatively pass their data through the network to a main location. For that reason, the multicast in wireless networks is anticipated to lay concrete on the way for efficient group communications, by which many group-based applications, such as charged video on demand or video conferencing, can be commercialized. In WSNs security, the key management problem is one of the most important and the most fundamental aspects. To attain security in wireless sensor networks, it is significant to be able to encrypt and authentication messages among sensor nodes. Before doing so, keys for performing encryption and authentication must be agreed upon by the communication nodes among the WSN. Nevertheless, due to the resource constrains on the sensor nodes, many key agreement mechanisms used in general networks, such as Diffie-Hellman and other public-key based schemes , are not feasible in sensor networks.